2022
DOI: 10.1038/s41598-021-03155-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diurnal phase on behavioral tests of sensorimotor performance, anxiety, learning and memory in mice

Abstract: Behavioral measurements in mice are critical tools used to evaluate the effects of interventions. Whilst mice are nocturnal animals, many studies conduct behavioral tests during the day. To better understand the effects of diurnal rhythm on mouse behaviors, we compared the results from behavioral tests conducted in the active and inactive phases. C57BL/6 mice were used in this study; we focus on sensorimotor performance, anxiety, learning and memory. Overall, our results show mice exhibit slightly higher cutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 26 publications
4
4
0
Order By: Relevance
“…Indeed, open field video-tracking revealed that distance traveled over time was elevated when 48 hr cycling animals were tested on days when they slept little (active days) compared to the alternating days of long sleep (inactive days) (Figures 2F-I). In contrast, no difference was found in Meth-naïve animals, when tested during their corresponding active (ZT12-18) and inactive (ZT0-6) phases in line with previous findings 20 (Figures 2K and 2L). Notably, distance traveled on active days in 48 hr cyclers was also greater when compared to Meth-naïve mice (Figure 2M), while there was no difference between inactive days and Meth-naïve animals (Figure 2N).…”
Section: Resultssupporting
confidence: 92%
“…Indeed, open field video-tracking revealed that distance traveled over time was elevated when 48 hr cycling animals were tested on days when they slept little (active days) compared to the alternating days of long sleep (inactive days) (Figures 2F-I). In contrast, no difference was found in Meth-naïve animals, when tested during their corresponding active (ZT12-18) and inactive (ZT0-6) phases in line with previous findings 20 (Figures 2K and 2L). Notably, distance traveled on active days in 48 hr cyclers was also greater when compared to Meth-naïve mice (Figure 2M), while there was no difference between inactive days and Meth-naïve animals (Figure 2N).…”
Section: Resultssupporting
confidence: 92%
“…The estrous stage, however, did not affect anxiety-like behavior in females assessed during the light period. Even though studies revealed mixed outcomes on the effect of daytime on anxiety-like behaviors ( Richetto et al, 2018 ; Meseguer Henarejos et al, 2020 ; Tsao et al, 2022 ), our results strongly support the view that time of day is a major factor in the regulation of anxiety-like behavior, and the deletion of clock genes in the striatum appears to attenuate this effect.…”
Section: Discussionsupporting
confidence: 81%
“…In mice kept in LD, the number of correct alternations in the Y-maze, which is dependent on hippocampal plasticity and related to exploratory activity [37], was significantly lower in the light phase than in the dark phase. This is consistent with the suppressive effect of light on activity in nocturnal animals [4], differences in effects of light and dark phase testing on behavioral readouts [42,43], and inhibition of behavioral and cognitive performance in the light phase [44] in mice. In contrast, when the mice were kept in DD to unmask circadian rhythms, there was no difference in the number of correct alternations in the Y-maze, although rhythmic spontaneous locomotor activity persisted.…”
Section: Effect Of Light/dark Cyclesupporting
confidence: 84%